2011
DOI: 10.1007/s00415-011-6236-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow characteristics in patients with post-lumbar puncture headache

Abstract: The aim of this study was to verify if diagnostic lumbar puncture (DLP) in post-lumbar puncture headache (PLPH) patients is related to significant changes in cerebral blood flow which could be visualized by transcranial Doppler (TCD). Sixty-six patients were enrolled in this study. TCD was performed 24 h before DLP and repeated within 24 h after the procedure. The measurements included mean velocity (Vmean), peak systolic velocity (Vmax), and Gosling’s pulsatility index (PI), in the left and right middle cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
(18 reference statements)
2
3
0
2
Order By: Relevance
“…In patients who developed PDPHs, the post-puncture values of Vm in both MCAs were significantly lower than the parameters before punctures. The decrease of Vm observed in this group of patients may result from the dilatation of intracranial vessels, a consequence of lowered ICP, so the findings of this study partially confirmed the theory behind the etiology of PDPHs [28]. Another study aimed to check whether hydration before puncture influenced the incidences of post-dural-puncture headaches and affected CBF in 99 patients enrolled for diagnostic lumbar punctures [43].…”
Section: Transcranial Doppler Studiessupporting
confidence: 67%
See 1 more Smart Citation
“…In patients who developed PDPHs, the post-puncture values of Vm in both MCAs were significantly lower than the parameters before punctures. The decrease of Vm observed in this group of patients may result from the dilatation of intracranial vessels, a consequence of lowered ICP, so the findings of this study partially confirmed the theory behind the etiology of PDPHs [28]. Another study aimed to check whether hydration before puncture influenced the incidences of post-dural-puncture headaches and affected CBF in 99 patients enrolled for diagnostic lumbar punctures [43].…”
Section: Transcranial Doppler Studiessupporting
confidence: 67%
“…In a study of 66 patients who required diagnostic lumbar punctures, CBF was assessed 24 h before and within 24 h after the procedures [28]. In patients who developed PDPHs, the post-puncture values of Vm in both MCAs were significantly lower than the parameters before punctures.…”
Section: Transcranial Doppler Studiesmentioning
confidence: 99%
“…Although not always associated pathologically, PDPH is usually associated with a reduced intracranial volume, downward brain displacement and compensatory increase in cerebral blood flow. 15,16 PDPH has the potential to cause significant morbidity, may persist for weeks [2][3][4]6 and is associated with chronic headaches. 17 The incidence of ADP from either an epidural or CSE in our teaching institution was 0.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Lybecker H y cols, realizaron 117 punciones lumbares de los cuales cinco desarrollaron CPPD, dos de tres casos tenían antecedentes de CPPD y tres de 114 casos sin este antecedente, demostrando en su estudio que el antecedente de CPPD es un factor predictor significativo para la patología (p=0,0018) 24 . Así mismo, la incidencia de CPPD es mayor en pacientes con antecedentes de cefalea, principalmente cefalea tensional 25 . Kuntz KM y cols, concluyeron que el grupo de pacientes con antecedentes de cefalea una semana previa a la punción dural tenía un incidencia de CPPD del 70% 7 .…”
Section: Antecedente De Cppd Y Cefaleaunclassified